EFEKTIVITAS PROBLEM-BASED LEARNING SETTING STAD DITINJAU DARI HASIL BELAJAR DAN DISPOSISI MATEMATIS MAHASISWA - Maria Trisna Sero Wondo; Konstantinus Denny Pareira Meke; Sofia Sao (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to describe the effectiveness of the STAD problem-based learning setting in terms of learning outcomes and mathematical dispositions. This research is an experimental research type of pre-experimental. This pre-experimental study used a one-group pretest-posttest design with a population of students in the second semester of the Mathematics Education Study Program at the University of Flores for the 2020/2021 academic year. The sample in this study was a class of second-semester students. The research instrument used was a test of learning outcomes in the form of a description of 6 questions and a non-test in the form of a mathematical disposition questionnaire in the form of a Likert scale with five answer choices. The data analysis technique used was the paired-sample t-test with the help of SPSS Windows Version 16. Based on the test results, obtained the value of sig. of 0.00 for learning outcomes and mathematical dispositions. This result shows that the problem-based learning setting of STAD is effective and good to be applied in the design of the learning process in a number theory course, in terms of learning outcomes and mathematical disposition abilities.